Dynamic accuracy model of porous journal air bearing considering rotational speed. (September 2021) - Zhang, Penghai; Zha, Jun
Abstract: In order to predict the high-speed error motion of the porous journal air bearing, a new dynamic accuracy model is established based on the simplified nonlinear air film force considering the rotational speed. Then the effect of the speed on the accuracy is discussed by the same averaging coefficient of quasi-static condition for various shaft and bush roundness errors. It finds that the speed only affects the amplitude of the error motion but doesn't affect its frequency information. As the speed increases, the averaging coefficient increases, while its frequency information is kept the same. The accuracy decreases with the increase of the speed. The model provides a low-cost way to predict the high-speed error motion by the low-speed error motion. Highlights: ● A new dynamic accuracy model of the porous journal air bearing is built based on the simplified nonlinear air film force. ● The effect of the speed on the error motion is studied by the same averaging coefficient of quasi-static condition. ● The speed only affects the amplitude of the error motion but doesn't affect its frequency information. ● As the speed increases, the value of the averaging coefficient increases, while its frequency information is kept the same. ● It provides a low-cost way to predict the high-speed error motion by the low-speed error motion.